Complementarity of labor market institutions, equilibrium unemployment and the propagation of business cycles - Michael C. Burda; Mark Weder (Hamburg Institute of International Economics (HWWA), 2001)
This paper evaluates complementarities of labor market institutions and the business cycle in the context of a stochastic dynamic general equilibrium model economy. Matching between workers and vacancies with endogenous time spent in search, Nash-bargained wages, payroll taxation, and differential support for unemployed labor in search and leisure are central aspects of the model. For plausible regions of the policy and institutional parameter space, the model exhibits more persistence than standard RBC models and can ex- hibit indeterminacy of rational expectations paths without increasing returns in production. Furthermore, labor market institutions act in a complementary fashion in generating these effects.
Keywords: 330; Arbeitslosigkeit; Arbeitsmarktflexibilisierung; Stochastisches Wachstumsmodell; Allgemeines Gleichgewicht; Real Business Cycle; Schätzung; Theorie; Deutschland; Vereinigte Staaten